Doomed to internationalization and modernization of corporate culture : The Russian experience of German firms - Anghel, Ghenadie (Gabler Verlag, 2012)
What kind of corporate- and intercultural problems do German companies encounter on the path towards globally operating enterprises? To what extent should they hold on to, adjust or abandon their long-established values and practices in a new business environment? What must they particularly expect while expanding into the Russian market? Ghenadie Anghel delivers answers to these questions on the basis of revealing interviews with general directors and senior executives of 27 Russian subsidiaries of large DAX-listed companies as well as medium-sized hidden champions.